CONTRADICTORY DUALS IN GHASSAN KANAFANI'S STORIES (A COLLECTION ABOUT MEN AND GUNS) AS A SAMPLE (American Journal of Research in Humanities and Social Sciences, 2024)
This study seeks, in its critical effort, to uncover the contradictory duals in Ghassan Kanafani's stories as a cognitive system that includes the depth of their presence in these stories and reflects a narrative awareness issued by the storyteller.Since these dualities expand with the expansion of Kanafani's narrative production, which makes this study inflated unjustifiably, the researchers decided to rely on the collection (On Men and Guns) as one of the most important collections of stories whose narrative system contains these dualities.These dualities – with what they include of aesthetic and intellectual dimensions – contributed significantly to the production of its artistic and semantic structure.